2011
DOI: 10.1038/onc.2011.144
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of PTEN expression by androgen receptor in prostate and breast cancers

Abstract: Prostate cancer and breast cancer are the most common malignancies in the western world. Androgen receptor (AR) and PTEN both have been well documented to have important roles in prostate carcinogenesis. In contrast, AR and PTEN in breast carcinogenesis have not been well studied. Furthermore, the crosstalk and connection between those two pathways remain unclear. Increased AR expression in prostate cancers, combined with decreased PTEN expression, portends a poor clinical outcome. Paradoxically, both high AR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 34 publications
2
64
1
Order By: Relevance
“…PTEN promoter (full-length, truncations and mutants) activity was measured by luciferase, and these constructs were made as defined in Ref. 22, and pRL-CMV Renilla reporter for normalization to transfection efficiency. Transient transfection was achieved using GeneFect (Alkali Scientific, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…PTEN promoter (full-length, truncations and mutants) activity was measured by luciferase, and these constructs were made as defined in Ref. 22, and pRL-CMV Renilla reporter for normalization to transfection efficiency. Transient transfection was achieved using GeneFect (Alkali Scientific, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…Unaromatizable androgens, such as dihydrotestosterone (DHT), inhibit tumor proliferation and induce apoptosis by activating androgen receptor (AR) in AR þ /ER þ breast cancers (7)(8)(9). Among all female breast carcinomas, 60% to 70% are AR positive.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor suppressor gene PTEN (deleted on chromosome 10) is one of the most frequently mutated or deleted genes in inherited and sporadic human cancers, including breast carcinomas (12). We have previously shown that AR is positively correlated with PTEN expression in breast carcinomas, which is due to the direct activation of PTEN transcription, mediated by an androgen response element (ARE) in the PTEN promoter (9,13).…”
Section: Introductionmentioning
confidence: 99%
“…However, P-AKT expression was increased in intraepithelial neoplastic glands, which were only present in ugePTENARKO. Therefore, in contrast to breast and prostate cancer cells (Wang et al 2011), the AR inactivation in uterine glandular cells did not appear to affect AKT signaling pathway. However, as intraepithelial neoplastic glands were only present in ugePTENARKO, further investigation (i.e., cell culture) is warranted to determine the direct role of glandular epithelial AR in AKT pathway.…”
Section: :5mentioning
confidence: 70%
“…Similarly, androgens may regulate ERα expression as shown by testosterone-induced suppression of ERα expression in mammary tissue (Zhou et al 2000). Alternatively, AR could interact with PTEN to indirectly modify ERα expression as seen in prostate and breast cancer cells (Wang et al 2011). Therefore, we explored whether glandular epithelial AR inactivation modified ERα expression in PTEN-deleted uterus.…”
Section: :5mentioning
confidence: 99%